Microalgae, a Potential Natural Functional Food Source – a Review - Villarruel-López Angélica; Ascencio Felipe; Nuño Karla (Polish Journal of Food and Nutrition Sciences)
Microalgae are a group of microorganisms used in aquaculture. The number of studies regarding their use as a functional food has recently increased due to their nutritional and bioactive compounds such as polysaccharides, fatty acids, bioactive peptides, and pigments. Specific microalgal glucans (polysaccharides) can activate the immune system or exert antioxidant and hypocholesterolemic effects. The importance of algal lipids is based on their polyunsaturated fatty acids, their anti-inflammatory effects, their modulation of lipid pathways, and their neuroprotective action. Microalgae peptides can bind or inhibit specific receptors in cardiovascular diseases and cancer, while carotenoids can act as potent antioxidants. The beneficial biological activity will depend on the specific microalga and its chemical constituents. Therefore, knowledge of the composition of microalgae would aid in identifying, selecting, and studying their functional effects.